Flood perception and mitigation: The role of severity, agency, and experience in the purchase of flood protection, and the communication of flood information - Soane, Emma; Schubert, Iljana; Challenor, Peter; Lunn, Rebecca; Narendran, Sunitha; Pollard, Simon J. T. (Pion Ltd, 2010)
Protection of human life and property from flooding is a strategic priority in the UK. We examine how to encourage home owners to protect themselves and their residences. A model of factors that influence the decision to buy flood protection devices is tested using survey data from 2,109 home owners. The results showed that the majority of respondents have not purchased domestic flood protection (N=1,732; 82.1%). Purchase of flood protection devices was influenced by age; perceived seriousness; and beliefs about, and trust in, the role of regulators in managing flooding. In younger respondents, the perceived seriousness of the dangers of flooding acted as precursors and barriers to action depending on individual sense of responsibility and agency. The second part of the study examined responsiveness to information. Information about flooding alone was insufficient to promote behavioural change, particularly among people who have not experienced a flood or who believe that they are not in a flood zone. Implications for understanding flood protection, managing agency issues, and flood communication campaigns are discussed.